A FabLab for development in rural Philippines: Reflecting on the recipe for success for a community technology center - Tomoaki Watanabe; Yutaka Tokushima (International Telecommunications Society (ITS), 2015)
This paper reports a participatory case study of a locally based digital technology center, a FabLab in Bohol, Philippines. A FabLab offers a range of digital fabrication technologies to the local public, which potentially can be used for creating tools for work, prototyping and manufacturing products for sale, and a wide range of other purposes. The technologies typically include 3D printer, laser cutter, CNC milling machine, and others. A FabLab abide by its Charter, including the principle of openness to the public at least some of its operating hours. One of the authors were involved in the launch of the place, and the process of help locals to take advantage of the technological capacities for improving their living conditions. The paper argues that keys to the success are not simply technological capabilities. The facility needs active users who are willing to connect technological capabilities, locally available skills and resources, and market opportunities or local problems causing less-than desirable living conditions. The chance of such matching to occur is not necessarily high for localities in general. In Bohol, it was not a process that happens easily. There were a group of people interested in improving quality of local life and local economy who actively explored matching possibilities to arrive at some working combinations. In addition, it is pointed out that the existence of inter-local connections, specifically the organizational proximity with another FabLab located in Indonesia served as a crucial catalyst for bringing about the development of local craft product. In a more abstract terms, the case in authors' view points to the possibility that successful ICT-enabled development occur not just because of technological capabilities, but because of active body taking charge of matching process and inter-local network serving to complement otherwise scarce human resources and skills and ideas embedded in them. In order to connect this case more with existing body of scholarship on ICTs for development, this paper compares the nature of FabLab with telecenters, more prevalent form of locally based community technology centers. Limitations of telecenters in terms of contributing to development seem to exist with two types of passivity. First, the users may remain passive users of information services provided online. Second, the facility may be a passive provider of capabilities waiting for users. This is close to a local library open to the general public, although telecenters are not bound to be a passive institution. FabLab Bohol seems to be active in the sense that users are not just consumers of service, but creators of things that they use or sell. It is also active in that the core members running the Lab are active match-makers.
Keywords: 330